Determinants of elephant distribution at Nazinga Game Ranch, Burkina Faso - Bernard Hien; Jonathan Jenks; Robert Klaver; Zeno Wicks (Pachyderm)
We used seasonal ground total counts and remote sensing and GIS technology to relate elephant (Loxodonta africana africana) distribution at Nazinga Game Ranch to environmental and anthropogenic factors. Variables used in analyses were normalized difference vegetation index, elevation, stream density, density of poaching and human illegal activities, distance to dams, distance to rivers, distance to roads, and distance to poaching risk. Contrary to our expectation, road traffic did not disturb elephants. Strong negative relationships were documented between elephant abundance and stream density, distance to dams, and poaching density. Density of poaching and other human illegal activities explained 81%, vegetation greenness 6%, and stream density 3% of the variation in elephant density. Elephant distribution represented a survival strategy affected by poaching, food quality and abundance, and water availability.